Fear and concerns of women delivering during coronavirus pandemic - Bahadur, Anupama; Mundhra, Rajlaxmi; Kuncham, Rupendra; Kashibhatla, Jyotshna; Verma, Neha; Chaturvedi, Jaya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Literature is sparse regarding the fears and concerns of women delivering during COVID 19 pandemic. We interviewed 12 women delivering during the initial first week of lockdown period. There were three key concern of women- fear of being exposed at hospital, restricted number of hospital visitors made them confined and self-isolated thereby making them bored and frustrated, risk of baby being infected. Virtual communication through mobile was seen as a major support in all serving as a means of contact with their loved ones. Understanding a pregnant women’s concern and fear during this pandemic will enable a health care worker in better counselling.